Urgensi Pelayanan Bimbingan dan Konseling Islam dalam Meningkatkan Emotional Bonding Remaja - Anggi Fitria; Iqbal Nuari; Thaheransyah Thaheransyah; Fadil Maiseptian (Empowerment Counseling Journal, 2025)
Emotional bonding plays a crucial role in adolescent development, influencing their psychological and social well-being. In Padang, adolescents face various emotional challenges that require a holistic approach. Islamic Guidance and Counseling Services (BKI) offer a solution based on spiritual values to support their emotional well-being. This article examines the urgency of BKI in enhancing emotional bonding among adolescents in Padang. The study aims to explore how BKI facilitates self-awareness, emotional regulation, empathy, and social skills development. The methodology includes a literature review and an analysis of BKI program implementation in educational institutions and religious organizations. The findings indicate that BKI effectively integrates Islamic values into counseling, helping adolescents manage emotions, enhance empathy, and strengthen social relationships. This article recommends expanding BKI programs to foster adolescents' emotional development more comprehensively, ensuring their psychological resilience and positive social interactions.